Answer:
B.
Step-by-step explanation:
Answer:
(-3, -3)
Step-by-step explanation:
1.) Rewrite the second equation so 3y is on one side of the equation:
3y=6+5x
2.) Substitute the given value of 3y (replacing 3y with 6+5x, since we know they equal each other) into the equation 17x=-60-3y
Should end up with this:
17x=-60-(6+5x)
3.) Solve 17x=-60-(6+5x)
Calculate Difference: 17x=-66-5x
Combine Like Terms: 22x = -66
Divided both sides by 22 to isolate and solve for x: -3
So We know x=-3, now we got to find the y value. We can use either the first or second equation to find y value, so lets use the second.
3y=6+5x
1.) We know that x=-3, so we can simply substitute x in the equation
3y=6+5x with -3
3y=6+5(-3)
2.) Solve 3y=6+5(-3)
Combine Like Term: 3y=6+-15
Combine Like Term Even More: 3y= -9
Divide by 3 on both sides to isolate and solve for y: y=-3
So now we know y=-3 and once again we know x=-3, so if we format that
(-3,-3)
^ ^
x y
Answer:
cost per pound = $4.20
Step-by-step explanation:
Cheese cost per pound = ?
first for the cost per pound
cost per pound = total cost / pounds bought
cost per pound = $10.50 / 2.5 pounds
cost per pound = $4.20
to check the above answer is correct
cost per pound = total cost / pounds bought
cost per pound = $12.60 / 3 pounds
cost per pound = $4.20
Therefor, the cheese costs $4.20 per pound.
The answer to your question is -10